Study on construction mechanic characteristics and construction optimization of super-large cross-section tunnel portal under shallow buried depth and asymmetrical loading: A case study in Southwest China - Hao Chen; Haozan Zheng; Bolong Liu; Man Huang; Jiawei Liu (PLoS ONE, 2025)
The excavation of the super-large cross-section tunnel portal section is prone to causing serious engineering distresses. The key factors to ensure the safe construction of portal section are to clarify the construction mechanic characteristics and select a reasonable construction scheme. In this paper, a bidirectional six-lane expressway tunnel in Southwest China was selected as an engineering case. Three excavation schemes, namely, the three-bench seven-step excavation method (TEM), the central diaphragm method (CDM), and the double side drift method (DSDM), were compared and analyzed. Findings revealed that due to the effect of the asymmetrically loaded and super-large cross-section, the surrounding rock deformation and supporting structure stress at the deep buried side were greater than those at the shallow buried side. The CDM and DSDM could reduce the tunnel span and provide temporary support in time, which could effectively control the surrounding rock deformation and improve the structural stress and the slope stability. According to the topographic condition, the excavation sequence of the DSDM was optimized. Excavating the shallow buried side drift first could alleviate the surrounding rock deformation and improve the slope stability in the early stage of construction. Finally, the optimal excavation scheme was successfully implemented.